Soft tissue non-Hodgkin lymphoma of shoulder in a HIV patient: a report of a case and review of the literature - Larocca Luigi Maria; Martini Maurizio; Magarelli Nicola; Cerciello Simone; Sgambato Alessandro; Marotta Domenico; Maccauro Giulio (World Journal of Surgical Oncology, 2008)
Abstract Background The risk of developing lymphoma is greatly increased in HIV infection. Musculoskeletal manifestations of the human immunodeficiency virus (HIV) are common and are sometimes the initial presentation of the disease. Muscle, bone, and joints are involved by septic arthritis, myopathies and neoplasms. HIV-related neoplastic processes that affect the musculoskeletal system include Kaposi's sarcoma and non-Hodgkin's lymphoma, the latter being mainly localized at lower extremities, spine and skull. Case presentation The Authors report a case of a 34 year-old lady. In December 2003 the patient noted a painless mass on her right shoulder whose size increased progressively. In March 2004 she was diagnosed HIV positive and contemporary got pregnant. The patient decided to continue her pregnancy and to not undergo any diagnostic procedure and treatment. At the end of August she underwent a surgical ablation of the lesion that revealed a lesion of 7 cm × 7 cm × 3,3 cm. The histology showed B-cells expressing CD20, PAX-5, CD10, BCL-6 and MUM-1 with 70% Ki67 positive nuclei. The lesion was also negative for EBV infection and showed a monoclonal rearrangement of IgH chain and a polyclonal pattern for TCR gamma and beta. A final diagnosis of diffuse large B-cell lymphoma was made. The patient underwent postoperative chemotherapy. At four-years follow up the patient is symptom free and no local nor systemic recurrence of pathology has been noted on MRI control. HIV infection is still under control. Conclusion In this report, we present a case of diffuse large B-cell lymphoma localized in the soft tissue of the shoulder in a HIV infected patient. Authors want to underline this case for the rare position, the big size and the association with HIV infection.